Analisis Determinan Nilai Ekspor Kopi Indonesia (Dampak Nilai Tukar Rupiah, Investasi Asing Langsung dan Harga Kopi Dunia) - Ni Putu Esti Utami Barsua; Nisrina Sekar Harum; Michael Angandowa Boeaya; Wimbi Uelsan Gurusinga (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Indonesia is one of the countries actively supporting export and import activities as a way to promote economic growth. In the agricultural sector, coffee is one of the leading commodities that plays a crucial role in overall non-oil export growth. This research aims to analyze the impact of the exchange rate of the rupiah, foreign direct investment (FDI), and world coffee prices on the export value of Indonesian coffee from 1990 to 2022. Time series data were obtained from the Central Statistics Agency, the World Bank, and previous studies. This study implements quantitative descriptive analysis using annual time series data for the period 1990-2022. The Error Correction Model (ECM) method is used to process the acquired data. The results show that the exchange rate does not affect the export value of Indonesian coffee from 1990 to 2022 in both the long and short terms. FDI has a positive impact on increasing the export value of Indonesian coffee from 1990 to 2022 in both the long and short terms. World coffee prices hurt the export value of Indonesian coffee from 1990 to 2022 in the short term, while in the long term, world coffee prices do not have a significant effect.